Academic Advisory Guidance Application Website-Based - Sukma, Fanni; Kasmar, Andre Febrian; Afyenni, Rita; -, Defni; Azizah, Nur (SOTVI, 2022)
Academic Advisory Guidance at the Information Technology Department Â Politeknik Negeri Padang is currently carried out manually, causing several obstacles, including time and place. To help with problems that occur, a website-based academic guidance system was built using the waterfall method. The stages of implementation methodology carried out are Analysis, System Design, Program Code Generation, and Program Testing. With this system, students and academic advisors can interact anytime and anywhere without having to meet face-to-face. This can also be a solution for students who have both academic and personal problems.